Persecution Act as Filter Bubble Effect: Digital Society and The Shift of Public Sphere - Arina Rohmatul Hidayah (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This article discusses persecution acts associated with the filter bubble effect, the condition of digital society, the concept of the public sphere and the rational action theory of Jurgen Habermas. The results, obtained through the literature research method, show that acts of persecution in social media can be caused by the personalization of the web. Social media allows the occurrence of large bubbles (filter bubbles) that make users reject ideologies or other truths. This becomes a revolution of mindset due to the freedom of information. Meanwhile, in the Habermas public sphere concept, which emphasizes the existence of a critical and rational discussion, this phenomenon indicates a shift. The shift that occurs brings about the lifeworld realm as the basis for the formation of the public sphere with its communicative action, again dominated by the system realm that is dominated by capitalist forces through strategic action. Thus, Habermas's initial goal of strengthening civil society's position against the dominance of the system is now changing.